How to Enhance Product Quality, Ad Credibility, and Location on Purchase Decisions - Khisamuddin, Muhammad Idrus; Ambarwati, Rita; Sari, Dewi Komala (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
The lifestyle needs of urban communities have made many business people develop their businesses in the food and beverage (F&B) sector. The proliferation and expansion of coffee shops can engender heightened business competitiveness, necessitating companies to consistently refine their marketing strategies to meet client satisfaction. The objective of this study is to assess the impact of Product Quality, Ad Credibility, and Location on Purchase Decisions about Starbucks Products. This research is causal research using quantitative methods. The study employed an incidental sampling technique, with a sample size of 96 respondents and a population size of up to 150 individuals. The data-gathering methodology employed in this study was the distribution of a questionnaire. The data analysis technique employed in this investigation involved the utilization of Smart-PLS Version 3.0. The variable of product quality demonstrates a statistically significant and favorable impact on consumer purchasing decisions within the context of Starbucks. In addition, the influence of advertising credibility and location on purchasing decisions at Starbucks is found to be beneficial, albeit not statistically significant.